LIFESTYLE MODIFICATION - IMPACT OF WALKING ON FASTING BLOOD SUGAR - SIRISHA, R; PARAMJYOTHI, PITTA (International Journal of Clinical and Biomedical Research, 2015)
Background: An average person is interested in staying healthy and general well-being. The present study was conducted to know the effects of walking on Fasting blood sugar in healthy individuals who changed their lifestyle by motivating them. Aim: The primary objective of present study is to identify the changes in Fasting Blood Sugar in normal subjects before and after walking for 30 minutes. Materials & Methods: The present study was conducted in the department of Physiology, Siddhartha Medical College, at Vijayawada Andhra Pradesh. A total number of 25 male and female adult healthy individuals were selected. Fasting Blood Sugar levels were compared before and after walking. Results: in this study significant change with p value 0.001 in Fasting Blood Sugar in normal healthy individuals before walking and 30 minutes after walking is observed. Conclusion: our study demonstrated small changes in daily life help to prevent diseases of modern civilization. KEYWORDS: Lifestyle; Fasting Blood Sugar; Walking.